POLITICAL ISLAM, TERRORISM AND SECURITY IN THE MIDDLE EAST - H. Jabbari Nasir (Vestnik MGIMO-Universiteta, 2017)
The article deals with the problem of politicizing Islam. The author states that Salafits’s approach to political domain of social being is at odds with original Islam. The article uses historical analysis in order to demonstrate different stages of politicizing Islam. The author also uses constructivist approach to show how radical Islamic ideologies are constructed.Until 19th century, Islam was a set of beliefs and social model but had no status of political system. However, due to externaland internal it gradually embarked on political path and started to acquire more active presence in various spheres of social life. Later new political culture was formed that constructed a new radical identity criticizing and even denying the existing norms of traditional Islam. Departing from many political, economic and cultural norms and referring to the holy Koran and Sunnah, radical Islamists aspire to establish an “ideal” or “pure” international society.The author concludes that the Neo-Salafists have transformed the traditional idea of jihad into an idea of global jihad and have made it their security manifesto. This leads to the globalizing effect which implies that regional security problems in theMiddle Eastare becoming the area of international community’s concern.